Nano Particle Reinforced Lead Free Sn–3.0ag–0.5cu Solder Paste For Reflow Soldering Process - Chellvarajoo, Srivalli (2016)

(untitled)
At present, researchers begin to reinforce nanoparticles into Pb free solders to develop high efficiency nanocomposite solders. The effects on nanoparticle reinforcement into SAC 305 after reflow to enhance the solder joint quality are focus of this research. Consequently, this investigation developed into parametric case studies on different type of ceramic nanoparticles (i.e., multielement oxide: Fe2NiO4, ITO; single element oxide: NiO, Fe2O3) and carbon-nanostructure (CN) particles (i.e., Diamond) as a manipulated variable (i.e., parameters) which are used to mechanically reinforce into SAC 305 solder alloys, respectively. The effects of these parameters on melting behavior, microstructures analysis (i.e., IMC thickness, nanoparticles motion during reflow), spreading rate, wetting angle and solder hardness after reflow have been analyzed. The correlations between the reinforced nanoparticles with the respective factors have been studied. From this research, it was identified that CN (i.e., Diamond) reinforced solder paste showed unique differences in the behavior and reached highest hardness with very little amount (i.e., 0.5wt.%) of reinforcement among the type of nanoparticles tested. As a result, diamond nanoparticles were used to extend the parametric studies with the mechanical tests (i.e., shear test and pull test). The effects of both shear and pull strengths towards different amount of diamond nanoparticles (0.01wt.%, 0.05wt.% and 0.1wt.%) with respective reflow profile were studied. The addition of 0.01wt.% diamond nanoparticles in SAC 305 solder enhanced the PCBA shear and pull force by 7.4 % and 26.4 %, respectively. Hence, the current study generates a new expectation on CN based nanoparticles to be reinforced in Pb free solder alloys to enhance package quality. The CN based nanoparticles required in little amount to homogeneously mixed in SAC 305 solder alloys and contribute improvement in solder joint quality. Moreover, it indirectly reduced the production cost and allocates valuable directions for the engineers and researchers in upcoming microelectronics industry.